Entinostat for the treatment of breast cancer. (3rd August 2017) - Trapani, Dario; Esposito, Angela; Criscitiello, Carmen; Mazzarella, Luca; Locatelli, Marzia; Minchella, Ida; Minucci, Saverio; Curigliano, Giuseppe
ABSTRACT: Introduction : Breast cancer accounts for 29% of malignant tumors. It is an heterogenous disease covering a spectrum of different molecular subtypes. Epigenetic aberrations may affect gene expression through DNA and histone proteins modifications thus promoting tumor progression and resistance to anti- tumor treatment. Area covered : This article explores the potential role of entinostat in the treatment of breast cancer. The clinical trials evaluating entinostat are discussed, highlighting preclinical data and early-phase clinical studies results. The emerging activity of entinostat in several clinical settings is evaluated by focusing on endocrine-resistant, HER2 positive and triple-negative breast cancer with promising activity in boosting the immune-system. Expert opinion : Entinostat, a synthetic benzamide derivative class I histone deacetylases (HDACs) inhibitor, inhibits cell proliferation and promotes apoptosis in breast cancer. Several results from clinical trials demonstrate that the addition of an epigenetic therapy to antiestrogen therapy may be an effective approach to targeting resistance pathways in breast cancer, particularly in hormone-positive disease. Agents such as entinostat may have a role in immunogenic modulation. Genetic and pharmacological inhibition studies identified HDAC as a key determinant in the reversal of carcinoma immune escape. This offers the rationale for combining HDAC inhibitors with immunotherapy, including therapeutic cancer vaccines.